Cyprus : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report ;, 2010)
Economic conditions have stabilized, and the economy is projected to bottom out in 2010, giving way to a mild recovery in 2011 followed by stronger growth. The foremost policy challenge is to achieve the official fiscal consolidation targets so as to put debt ratios on a declining path and provide more space to guard against risks to the financial sector. Further old-age pension reform is also essential. Structural reforms are needed to preserve competitiveness and enhance medium-term growth. The government largely shared the IMF staff's assessment.